Shock contagion, asset quality and lending behavior - Tho Pham; Oleksandr Talavera; Andriy Tsapin (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
This paper exploits the geopolitical conflict in Eastern Ukraine as a negative shock to banking sector and examines the shock transmission. We find that banks with more loans in the conflict areas during the pre-conflict period face a higher level of bad loans in other markets after the shock. This effect is stronger in the regional markets which are closer to the conflict zone. We also find evidence for the "flight to headquarters" effect in post-conflict lending. Specifically, while more affected banks tend to cut their credit supply, the larger contraction is observed in regional markets located farther from headquarters.
URN:NBN:fi:bof-201811292147
Keywords: G01; G21; 330